Enhancing Quality Education Through Cooperative Learning in Remote Area - Mustakim Mustakim; Ita Sarmita Samad; Umiyati Jabri; Ismail Ismail; Elihamid Elihamid (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Access to quality education in remote areas remains a global challenge, particularly in achieving Sustainable Development Goal 4 (SDG 4). This study explores the effectiveness of cooperative learning strategies in addressing educational disparities faced by students in rural communities in South Sulawesi, Indonesia. A qualitative approach was employed, involving semi-structured interviews with 12 teachers and 24 students from four public junior and senior high schools in isolated mountainous villages. Classroom observations were also conducted to triangulate the data. Thematic analysis revealed that cooperative learning enhanced studentsÔÇÖ critical thinking, encouraged active participation, and improved peer collaborationÔÇöespecially when supported by teacher facilitation, culturally relevant materials, and low-tech group projects. However, challenges such as limited access to learning materials, unstable electricity, and language diversity emerged as barriers. Students shared that working in groups helped them ÔÇ£grasp difficult topicsÔÇØ and ÔÇ£build confidence to express opinions.ÔÇØ The study underscores the potential of cooperative learning to reduce educational inequality in under served regions, while also highlighting the need for longitudinal research on the integration of emerging technologies such as AI and VR in remote settings. The findings provide practical recommendations for educators, policymakers, and stakeholders committed to inclusive and sustainable rural education aligned with SDG 4.